Development of the International Classification of Functioning, Disability and Health core sets for traumatic brain injury: An International consensus process. (April 2013) - Laxe, Sara; Zasler, Nathan; Selb, Melissa; Tate, Robyn; Tormos, José M.; Bernabeu, Montserrat
<x xml:space="preserve">Abstract</x> Background: In a patient-oriented healthcare system, the integration of the functional status of the patient from the perspective of different professionals is understandable by the use of the International Classification of Functioning, Disability and Health. Objective: A formal decision-making and consensus process is presented to develop the first version of the International Classification on Functioning, Disability and Health (ICF) Core Sets for Traumatic Brain Injury. Method: A panel with the results from preparatory studies that included a literature review, a qualitative study, empirical data collection and an expert survey, was presented. A consensus conference was held in Barcelona, March 2010 and 23 professionals attended representing nine countries. Results: The preparatory studies identified 183 eligible categories. After the voting process, 139 constituted the Comprehensive Core Sets for TBI and 23 the Brief Core Sets for TBI. Conclusions: The consensus conference led to the integration of evidence and expert opinion based on the ICF. The adoption of the ICF Core Sets for TBI provides a basic international standard for the multidisciplinary assessment of a TBI patient's functioning.